Sosialisasi Identitas Kependudukan Digital Dalam Meningkatkan Partisipasi Masyarakat Kota Samarinda Pada Revolusi Digital - Muhammad Khumaidi Nursyarif; Muhamad Wahyu Tirta; Tri Wahyudi; Siti Patimah; Siti Muawwanah; Arbansyah Arbansyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Digital Revolution is driving the transformation of population administration in the city of Samarinda through the Integration of Digital Population Identity (IKD). This study evaluates the socialization strategies of IKD and their impact on community participation. Through collaboration in Kaltim Fest, hospitals, and campuses, the program focuses on the activation of IKD and engagement with relevant institutions. The enthusiasm of the community in participating in activities highlights awareness and acceptance of IKD. The research results provide a foundation for further development, strengthening the role of IKD in population services